PENERAPAN HACCP DALAM PROSES PRODUKSI MENU DAGING RENDANG DI INFLIGHT CATERING - Ardanisworo Lintang Wicaksani; Retno Adriyani (Media Gizi Indonesia, 2017)
HACCP is one of the food safety systems which is done by analyzing materials, processes, and food products. HACCP  analysis can be used as an effort to control the quality of the ﬁ nal product in order to meet the requirements of healthy, safe and halal food products. PT X is a catering company for aircraft service users (inﬂ ight catering). This company has implemented HACCP in every food production. This is a descriptive research by observing the process of rendang meat production. The application of HACCP in PT. X is done by controlling temperature and time during production process to prevent microbes growth. From ten application of HACCP according to SNI No. 01-4852-1998 about HACCP there is a point that has not been accordance with SNI monitoring. Monitoring activities are not routinely performed on blast chilling and dishing process. Pieces of coconut milk’s pack fall in to the pan when cooking process because the cutting of coconut milk pack is done on the cooking pan. Other HACCP principles like HACCP team determination, product description, ﬂ ow chart reaction, hazard identiﬁ cation, critical point determination, critical boundary determination of each CCP, corrective action, microbiological veriﬁ cation, and documentation are well implemented.